Brottsligheten och fängarnas psykosociala bakgrund - Vilho J. Mattila; Raimo K. R. Salokangas; Vilho I. Jäppinen; Matti I. Joukamaa; Lauri Salmi; Hannu Holm (Nordisk Tidsskrift for Kriminalvidenskab)
See abstract in article.